Electrifying White Biotechnology: Engineering and Economic Potential of Electricity‐Driven Bio‐Production. Issue 5 (10th December 2014) - Harnisch, Falk; Rosa, Luis F. M.; Kracke, Frauke; Virdis, Bernardino; Krömer, Jens O.
Abstract The production of fuels and chemicals by electricity‐driven bio‐production (i.e., using electric energy to drive biosynthesis) holds great promises. However, this electrification of white biotechnology is particularly challenging to achieve because of the different optimal operating conditions of electrochemical and biochemical reactions. In this article, we address the technical parameters and obstacles to be taken into account when engineering microbial bioelectrochemical systems (BES) for bio‐production. In addition, BES‐based bio‐production processes reported in the literature are compared against industrial needs showing that a still large gap has to be closed. Finally, the feasibility of BES bio‐production is analysed based on bulk electricity prices. Using the example of lysine production from sucrose, we demonstrate that there is a realistic market potential as cost savings of 8.4 % (in EU) and 18.0 % (in US) could be anticipated, if the necessary yields can be obtained.